The Value of Digital Communication - Kamilla R. Nigmatullina (Гуманитарный вектор)
The publication is devoted to the value foundations of mass communication on the sites of local news media in social networks. The relevance of the work is related to the growth of news media audiences on digital platforms and the need to involve subscribers in the life of communities based on common values. Scientific novelty is expressed in the analysis of the still unexplored formation of local communities and their values on digital platforms. The author poses the question of harmonizing communication based on constructive values, as well as the values of communication itself that support media in social ecosystems: involvement, exchange of emotions based on information, ease of demonstrating support or disapproval, direct communication with opinion leaders. The general problem of the research is designated as the axiological ambivalence of communication in the digital environment. The work used a systematic review of the literature and a qualitative generalization of the results of the author’s previous studies related to the practice of local communities on digital platforms. The review showed the presence of common characteristics for all the results obtained. Among them is the imbalance of communication depending on the region and local politics, as well as the presence of negative emotions and fake information in communications, while people tend to spread negative content of posts / actively react to them. Finally, the volume of communication itself on social networks is uneven in specific topics, periods of time and for audiences of different regions.The study showed that the value of communication in local media on digital platforms lies in the ability of messages to form values that unite the audience and neutralize radicalizing ones, to form a constructive discussion (with the search for solutions to the conflicts that have arisen), taking into account the different value foundations of the communication participants. The values of local communities are concentrated not only around local patriotism, civic activism and proactivity ‒ the named triad is able to harmonize radicalized discussions on digital platforms.